Perturbed Lamé equation and the Buslaev phase - Tajima, S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the perturbed Lamé equation with 1-zone potential and give an explicit description of the geometric phase that is contained in the leading term of the series of an asymptotic solution.